2011
DOI: 10.1108/13664381111153132
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the financial performance of green buildings in the UK commercial property market

Abstract: Purpose -Given the centrality of data and information to the evaluation and operation of policies to reduce carbon emissions, the purpose of this paper is to investigate potential sources of data within in the UK on the commercial building stock in terms of its physical characteristics, financial performance, energy consumption and environmental performance. The research aimed to increase understanding of the potential sources of data on property attributes, financial performance and energy use or environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…In Europe, the Energy Performance in Buildings Directive has moved mandatory energy performance disclosure to the forefront of the energy and climate change policy agenda (Berry et al, 2008), requiring all buildings at construction, sale or rent to have certificates providing information about their energy performance, through a rating based ultimately on an assessment of CO 2 emissions. The Energy Performance Certificates (EPCs) which are the result of this policy are intended to inform potential buyers or occupiers about the intrinsic energy performance of a building (Fuerst et al, 2011). The principle underlying the Directive is to provide accurate and standardised information relating to inherent building energy efficiency to the market place, in order to change consumer behaviour and permit prospective owners, occupiers and tenants to recognize and integrate energy efficiency characteristics in determining value (Davis et al, 2015).…”
Section: Absractmentioning
confidence: 99%
“…In Europe, the Energy Performance in Buildings Directive has moved mandatory energy performance disclosure to the forefront of the energy and climate change policy agenda (Berry et al, 2008), requiring all buildings at construction, sale or rent to have certificates providing information about their energy performance, through a rating based ultimately on an assessment of CO 2 emissions. The Energy Performance Certificates (EPCs) which are the result of this policy are intended to inform potential buyers or occupiers about the intrinsic energy performance of a building (Fuerst et al, 2011). The principle underlying the Directive is to provide accurate and standardised information relating to inherent building energy efficiency to the market place, in order to change consumer behaviour and permit prospective owners, occupiers and tenants to recognize and integrate energy efficiency characteristics in determining value (Davis et al, 2015).…”
Section: Absractmentioning
confidence: 99%
“…Higher rated buildings may have been located in higher value locations within urban areas and/or have superior construction and/or specification. For instance, the only quality variable included in one of the models is condition and it is notable that, when it is included in the model, the estimated premiums drop substantially (Fuerst et al, 2011, Fuerst and McAllister, 2011a, Kok and Jennen, 2011.…”
Section: Related Researchmentioning
confidence: 99%
“…The feasibility and quality of empirical research into the effect of environmental input on the output of economics of real estate value depends heavily upon access to comprehensive and disaggregated data. as Byrne (2005) andfuerst et al (2011) indicated, despite several agencies holding data for aggregated market trend and index purposes, this data is not available or sufficient for the analysis of individual locations, especially for detailed and specific environmental studies in the context of commercial properties. research also suggests that even when data is available the impact of flooding on market value is difficult to assess from the current market due to causes such as imperfect information, risk perception and differences in availability of insurance (Lamond et al 2010).…”
Section: Introductionmentioning
confidence: 99%